Critical–Reflective Self-Assessment in Clinical Activities in a Dentistry Program at a Brazilian Public University - Luís Eduardo Genaro; Aylton Valsecki Júnior; Silvio Rocha Corrêa da Silva; Elaine Pereira da Silva Tagliaferro; Fernanda Lopez Rosell (Dentistry Journal, 2025)
Objectives: This study aimed to analyze the critical and reflective self-assessment capacity of dentistry students based on two clinical courses that employ self-assessment processes as a strategy to foster autonomy in health care. Materials and Methods: Reflections from third- and fifth-year students were evaluated over a three-year period. The methodology sought to identify the presence of critical reflections, perceptions of strengths and weaknesses, and the formulation of improvement plans. Results: The results revealed low levels of continuous reflection, with only 20.0% of third-year students and 24.1% of fifth-year students engaging in reflection in at least half of their clinical activities. However, 78.7% of third-year students and 90.8% of fifth-year students completed at least one reflection during the academic year. The ability to sustain continuous critical reflection was observed in only 22.1% of the 453 students evaluated. These findings present a concerning scenario, as critical reflection is directly linked to competence in health care and informed decision-making. Conclusions: The study concludes that formative assessment processes requiring critical and reflective self-assessment must be broadly integrated into the curriculum to foster significant gains in the development of professional competencies.